2017
DOI: 10.3311/ppch.10689
|View full text |Cite
|
Sign up to set email alerts
|

Novel Solid Base Catalyst Derived from Drinking Water Defluoridation for Biodiesel Synthesis

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…The homogeneous catalysts that are often used are NaOH and KOH. These catalysts give good biodiesel yield, but they are also tough to isolate, wash, and reuse as compared with heterogeneous catalysts …”
Section: Introductionmentioning
confidence: 99%
“…The homogeneous catalysts that are often used are NaOH and KOH. These catalysts give good biodiesel yield, but they are also tough to isolate, wash, and reuse as compared with heterogeneous catalysts …”
Section: Introductionmentioning
confidence: 99%
“…Their research revealed that about 93% biodiesel yield is achievable by using 1 wt% dose of derived catalyst in the methanolysis of soybean oil. In addition to water scales, water sludge obtained during defluoridation process can also be synthesized into solid base catalyst for biodiesel production as suggested by Gupta et al (2017). Eggshell is a semi-permeable membrane entirely made of calcium carbonate (in calcite form).…”
Section: Waste Water Scalementioning
confidence: 99%